The impact of renal sympathetic denervation on cardiac electrophysiology and arrhythmias: A systematic review of the literature. (1st October 2016) - Bazoukis, George; Korantzopoulos, Panagiotis; Tsioufis, Costas
Abstract: Introduction: Increased central sympathetic activity has a central role in the pathophysiology of cardiac arrhythmias. Despite the recently published negative results regarding the impact of renal sympathetic denervation (RDN) on resistant hypertension treatment, the beneficial effects of this intervention on cardiac arrhythmias seems to be promising. The aim of this systematic review is to analyze the existing data regarding the impact of RDN on atrial and ventricular arrhythmias. Methods: We systematically searched MEDLINE/PubMed database until January 2016 by using the algorithm "renal denervation AND (arrhythmias OR atrial OR ventricular)" without limitations. Additionally, the reference lists of the included studies and the relevant review studies were also manually searched. Results: Of the 467 studies yielded from the initial search, 34 were finally included in the systematic review (15 human studies, 18 animal studies and 1 study with both experimental and clinical data). The critical analysis of data from both human and animal studies indicates that RDN can modulate atrial and ventricular electrophysiological properties and exerts favorable effects in the development and recurrence of atrial and ventricular arrhythmias. Conclusion: In this systematic review we showed that RDN reduces the burden of atrial and ventricular arrhythmias in various experimental and clinical settings. Appropriately designed randomized sham controlled trials are needed in order to elucidate the exact impact of RDN on arrhythmia management. Highlights: Renal denervation decreases cardiac sympathetic activity. Decreased sympathetic activity favorably affects atrial and ventricular remodeling. Renal denervation reduces the burden of atrial and ventricular arrhythmias.